Glass ceiling in succession planning of women in management positions - لیلا الماسی; زهرا لبادی; وحیده علیپور (Allameh Tabataba'i University Press, 2015)
This research focuses on studying the glass ceiling for women in leadership positions in succession planning and promotion of administrators and education experts in Alborz Province. The method of this research is Descriptive - survey. The population of the study is included all male and female managers, top executives and managers and all staff employed in the Office of the Alborz Province and all eight eight regions of the Alborz Province. The population in 1806 is based on single-sample of 317 participants who were selected through Cochran formula for contingency. The instrument was a questionnaire that was developed based on the literature study and has used face validity for validity of instrument and also has asked the opinion of experts for content validity.Cronbach's alpha was used for reliability studies of the value of 95% was achieved, the collected data were analyzed by Univariate regression test and Friedman rank test. The data showed the organizational, cultural, and political factors in order of importance and greater impact on creating a glass ceiling and the family has the lowest impact factor.